2019
DOI: 10.1016/j.neuroimage.2018.10.079
|View full text |Cite
|
Sign up to set email alerts
|

How do spatially distinct frequency specific MEG networks emerge from one underlying structural connectome? The role of the structural eigenmodes

Abstract: Functional networks obtained from magnetoencephalography (MEG) from different frequency bands show distinct spatial patterns. It remains to be elucidated how distinct spatial patterns in MEG networks emerge given a single underlying structural network. Recent work has suggested that the eigenmodes of the structural network might serve as a basis set for functional network patterns in the case of functional MRI. Here, we take this notion further in the context of frequency band specific MEG networks. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 72 publications
4
88
1
Order By: Relevance
“…One of the main goals of brain network analyses is to understand the structural underpinnings of the functional organization of the human brain. Functional networks generated from magnetoencephalography or electroencephalography data have revealed that the strength of functional connections between brain areas depends on the frequency of the signals (Brookes et al, 2011;Deco et al, 2017;Messaritaki et al, 2017;Tewarie et al, 2019). Additionally, they have shown that there may be more than one mechanism of coupling between brain areas, such as phasephase, phase-frequency, phase-amplitude and amplitude-amplitude (Hyafil et al, 2015;Dimitriadis et al, 2015;Dimitriadis and Salis, 2017;Dimitriadis, 2018;.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main goals of brain network analyses is to understand the structural underpinnings of the functional organization of the human brain. Functional networks generated from magnetoencephalography or electroencephalography data have revealed that the strength of functional connections between brain areas depends on the frequency of the signals (Brookes et al, 2011;Deco et al, 2017;Messaritaki et al, 2017;Tewarie et al, 2019). Additionally, they have shown that there may be more than one mechanism of coupling between brain areas, such as phasephase, phase-frequency, phase-amplitude and amplitude-amplitude (Hyafil et al, 2015;Dimitriadis et al, 2015;Dimitriadis and Salis, 2017;Dimitriadis, 2018;.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how flexible macroscopic functional architecture arises from the stable scaffold of anatomical white matter fiber tracts in the brain is a major field of inquiry in neuroscience. This has been investigated via the relationship between structural and functional connectivity (SC and FC, respectively) between brain regions in fMRI and MEG (Abdelnour, Dayan, Devinsky, Thesen, & Raj, 2018;Atasoy, Donnelly, & Pearson, 2016;Cabral et al, 2014;Damoiseaux & Greicius, 2009;Deco et al, 2013;Glomb, Ponce-Alvarez, Gilson, Ritter, & Deco, 2017;Goñi et al, 2014;Hagmann et al, 2008;Honey et al, 2009;Meier et al, 2016;Tewarie et al, 2019Tewarie et al, , 2014Vincent et al, 2007) . Concurring findings from these studies show that FC between regions of interest (ROIs)/sources located in the gray matter is in part shaped by anatomical connections of the SC, such that the strength of SC (fiber count, density) is predictive to some degree of the strength of FC (correlation, coherence, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This result evidences the limitations of classical power spectral analysis, while possing interpretations issues: three different results related to three different frequency bands that must be discussed. The interpretation of different band-specific results emerging from a single structural network is still an ongoing debate [42]. On the contrary, the analysis proposed in this work does not rely on classical frequency bands, offering a single result.…”
Section: Discussionmentioning
confidence: 92%